Occurrence and characteristic of microplastics in suspended particulate, a case study in street of Yogyakarta - Jannah, Baiq Raudatul; Maharani, Hanifa Aulia; Rahmawati, Suphia; Nugroho, Adam Rus; Norhidayah, Abdull (EDP Sciences, 2024)
Microplastics (MPs) are increasingly recognized as emerging pollutants affecting the hydrosphere, geosphere, and atmosphere. One of the primary suspected sources of MPs is road dust in urban areas, with the majority originating from transportation, such as vehicle tires and road marking paint. MPs with a size of less than 5 mm can be ingested by humans from the air, and their potential effects remain largely undiscovered. There is still limited research on MPs in the air, particularly in Yogyakarta, one of the major cities in Indonesia. This study approach MPs as suspended particulates and, as such, employed a High Volume Air Sampler (HVAS) to collect air samples for Total Suspended Particulates TSP, PM2,5 and PM10 in four locations with high human activity and traffic volumes in Yogyakarta. A digital microscope was used to identify the number, shapes, and colors of the MPs. The results revealed 4576 particles of MPs in all the samples, with East Ringroad having twice the number of MPs compared to West Ringroad. The order of occurrence in terms of shapes was as follows: fragments (39%), films (37%), and fibers (25%). In terms of color, black was the dominant color of MPs, followed by brown and transparent. These results suggest a significant presence of black, fragmented-shaped MPs, which could indicate that most MPs in the ambient air near Yogyakarta's roads originate from vehicle activity, consistent with previous findings. Furthermore, the high number of colored fibers and films may indicate packaging and fabric degradation in the surrounding area.